Hybrid Contracts in Islamic Financial Institutions: An Analysis of Multi-contract Models - Musfiqoh, Siti; Sukamto, Sukamto (Institut Agama Islam Negeri Kendari, 2024)
This study examines the development of multi-contract and parallel transaction models in Islamic financial institutions, focusing on the concept of hybrid contracts. As Islamic banking faces increasingly complex challenges, there is a growing need for innovative products that comply with Shariah principles while meeting modern business demands. The research employs a qualitative approach with descriptive analysis to explore the theoretical foundations, practical applications, and regulatory considerations of multicontracts in Islamic finance. The study identifies various models of hybrid contracts, including murabahah, musyarakah mutanaqishah, and ijarah, and analyzes their implementation in Islamic banking products. It also discusses the jurisprudential debates surrounding the permissibility of multi-contracts, highlighting the conditions and limitations set by Islamic scholars. The findings reveal that while multi-contracts offer solutions for product innovation in Islamic finance, their application must be carefully structured to avoid prohibited elements such as riba and gharar. The study concludes that the development of multi-contract models requires a balance between financial innovation and adherence to Shariah principles. This research contributes to the understanding of complex Islamic financial instruments and provides insights for practitioners, regulators, and researchers in the field of Islamic banking and finance.